Investigasi Hubungan Antara Resiliensi Akademik, Mindfulness dan Efikasi Diri Akademik Siswa SMP Se-Kota Surabaya - Puspitasari, Yuanita; Darminto, Eko; Tri Hariastuti, Retno (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
Academic resilience, mindfulness, and academic self-efficacy are topics of interest to psychologists, but little is known about the relationship between the three. The main aim of this study was to explore the role of mindfulness and academic self-efficacy in predicting academic resilience among junior high school students. This research design uses quantitative correlation. The subjects in this study were 710 junior high school students in Surabaya. The research instrument used the Freiburg Mindfulness Inventory questionnaire, the academic self-efficacy questionnaire and the Casidi academic resilience questionnaire. The data analysis technique uses multiple regression techniques. The results showed that there was a significant relationship between mindfulness and academic self-efficacy, r = 0.43. Both mindfulness and academic self-efficacy were found to be significant predictors of academic resilience, F (1.139) = 110.39, p<.000, and F (2.138) = 104.44, p<.000. Based on the results of the study it can be concluded that mindfulness and academic self-efficacy have a significant influence on the academic resilience of junior high school students.